SPS portal - Mohd Azfar Shahir, Ishak; Abu Rashidin, Mohidin; Norhayati, Ahmad Rosli (Universiti Malaysia Sarawak (UNIMAS), 2004)
This portal is design for the e-government that includes the information about the organization. Realizing the needed of portal in government organization, we searching for organization that want the portal build in their organization. The portal for government has its own policies, standards and guideline. The use of this portal would help user such as citizen and employees to find to useful information and services. It also provides us the ability dealing with real client in real world.